TECHNOLOGY INNOVATION HOLDS THE KEY TO VICTORY FOR THE FASHION INDUSTRY’S BRIGHT FUTURE. - Shah, Vikita; Agarwal, Smriti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fashion sector has been in the forefront of implementing cutting-edge technologies for the last ten years. From the first sewing machine uses for fabric creation to cutting-edge developments like biodegradable fabrics, fashion rental applications, and even needle-free stitching processes, this evolution covers it all. As technology is advancing rapidly in today’s world, the arrival of artificial intelligence represents a major turning point in the industry. Notably, artificial intelligence (AI) is increasing production efficiency in the fashion industry, augmented reality is improving the customer shopping experience, and virtual platforms are boosting the industry’s economy. Among the most recent technological developments, artificial intelligence is noteworthy when considering evolution. AI is revolutionizing the fashion business by driving efficiency out of large-scale production processes. The current state of technology in the sector is unparalleled. The fashion industry has been at the forefront of using cutting-edge technology during the past ten years. The fashion business has undergone many advances in the previous few years, including the introduction of needleless sewing, biodegradable materials, sewing machines for fashion products, and fashion rental apps. Artificial intelligence marks the beginning of fashion evolution. The usage of technology in fashion is at its peak right now. Technology includes artificial intelligence, which is increasing the fashion manufacturing industry’s production capacity; augmented reality, which improves the shopping experience for customers; and virtual outlooks, which raise the fashion industry’s remunerative economy. Artificial intelligence is the newest technological advancement when it comes to evolution. There has never been more technology in fashion as there is right now. Large production lines are being optimized by artificial intelligence, consumer experiences are being improved by augmented reality, and profitable new revenue streams are being created by the virtual world. One of the most obvious changes in the fashion sector is attributed to e-commerce. Online shoppers are becoming more and more accustomed to its convenience. Innovative digital strategies have been adopted by fashion firms to establish a connection with their target audience. Among these cutting-edge technology are virtual fitting rooms, which let buyers make more rash selections by showing them how a product would seem on their particular body type. To improve efficiency, artificial intelligence is also being used in the design process. For instance, designers can use it to digitally resize clothes without having to make them, change colors, and even create visual backdrops that give buyers a clear idea of how a garment will look in general. This method conserves materials and time. E-commerce has caused one of the most noticeable shifts in the fashion business. Online purchasing is getting increasingly popular due to its convenience. Fashion brands are starting to use cutting-edge digital strategies to connect with their target market. Virtual fitting rooms, one of the more sophisticated technologies, allow buyers to try on clothing and see how it fits their body type, which encourages more impulsive decision-making. Artificial intelligence (AI) is used in the fashion design process to make the process much simpler. For example, AI can be used to digitally resize a garment without actually making it, change its color digitally, and create a visual backdrop that will allow the buyer to make an accurate judgment about the garment’s overall appearance. This conserves resources and time, which The introduction of 3D printing is a huge technological advancement that enables firms to reach a wider customer base. Furthermore, automation is essential for increasing output rates. Innovative production processes, like digital pattern-making procedures, computerized laser cutting equipment, and design software, are also revolutionizing the fashion business.